Influence of body position on maximum bite force - Guimarães, Élcio Alves; Cabral, Alana Leandro; Sousa, Lucas Resende; Júnior, Paulo Cézar Simamoto; Sousa, Gilmar da Cunha; Neto, Alfredo Júlio Fernandes (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Objective: To evaluate the maximum bite force (MBF) in subjects with and without Temporomandibular Dysfunction (TMD), in three different positions (sitting, lying and standing). Methods: The sample consisted of 60 individuals, aged between 19 and 35 years, who were divided into two groups: with TMD (n = 30) and without TMD (n = 30). First, the RDC/TMD questionnaire was applied and, after diagnosis, all of the subjects selected were submitted to the measurement of MBF, on each side (right and left), in three different positions (sitting, lying and standing), by means of a digital gnatodynamometer. Results: No significant difference in mean MBF was found between the two groups; however, the mean MBF for the subjects, comparing the same side and different positions, was significantly different, being smaller when the individual was lying down. Conclusions: According to the results, it was concluded that the MBF is influenced by the change of position.